2016
DOI: 10.1111/jfpp.13079
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ultrasonic Waves in Bleaching of Olive and Sunflower Oils and Comparison with Conventional Bleaching

Abstract: This study was aimed to bleach olive and sunflower oils by using conventional and ultrasonic methods. The qualitative and quantities characteristics of the bleached oils were compared. The used ultrasonic bath (150 W, 20 kHz) was set at two levels of temperatures (45 and 60C). Series of tests including of chlorophyll and carotenoid, color, peroxide value, acidity measurements and free fatty acid (FFA) determination were carried out. By application of conventional bleaching a considerable reduction in chlorophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…Sunflower oil is not known for its high carotenoid content compared with other vegetable oils. Gunstone (2011) reported the carotenoid content of sunflower oil to be between 1 and 1.5 mg/kg, while Abbasi et al (2017) reported it as 5.95 mg/kg. In this study, the carotenoid content was found to be 2.37 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Sunflower oil is not known for its high carotenoid content compared with other vegetable oils. Gunstone (2011) reported the carotenoid content of sunflower oil to be between 1 and 1.5 mg/kg, while Abbasi et al (2017) reported it as 5.95 mg/kg. In this study, the carotenoid content was found to be 2.37 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Abbasi ve diğ. [54], yaptıkları çalışmada ayçiçeği ve zeytinyağında geleneksel ve ultrases destekli renk açma işlemi uygulamışlardır. Ultrases destekli renk açma işlemi ultrasonik banyoda, 2 farklı sıcaklık (45 ve 60 °C) ve 3 farklı süre (10-20-30 dk.)…”
Section: Renk Açmaunclassified
“…Этот факт ограничивает температуру магнито-ультразвуковой обработки и требует немедленного охлаждения полученных продуктов разделения. Магнитная обработка может дать положительный антиокислительный эффект не только в дальнейшем при хранении погонов, но также в технологических процессах нейтра-лизации, отбелки и дезодорации погонов [9][10][11][12]. Поэтому для снижения кислотности и цветности жидких продуктов процесс ведем в присутствии силикагеля марки КСК [7].…”
Section: выбор и обоснование способов модификации фосфатидных концентunclassified